2007
DOI: 10.1016/j.cell.2007.05.058
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ Suppression of TSC1 Links Inflammation and Tumor Angiogenesis via the mTOR Pathway

Abstract: TNFalpha has recently emerged as a regulator linking inflammation to cancer pathogenesis, but the detailed cellular and molecular mechanisms underlying this link remain to be elucidated. The tuberous sclerosis 1 (TSC1)/TSC2 tumor suppressor complex serves as a repressor of the mTOR pathway, and disruption of TSC1/TSC2 complex function may contribute to tumorigenesis. Here we show that IKKbeta, a major downstream kinase in the TNFalpha signaling pathway, physically interacts with and phosphorylates TSC1 at Ser4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
522
7
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(570 citation statements)
references
References 40 publications
26
522
7
10
Order By: Relevance
“…In addition, colocalization of caveolin-1 and b-catenin was observed (Figure 4a). Therefore, overexpression of caveolin-1 might stabilize the E-cadherin/b-catenin complex on membranes by suppressing the phosphorylation of b-catenin, which negatively regulate the interaction between E-cadherin and b-catenin (Piedra et al, 2003;Lee et al, 2007;Tominaga et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, colocalization of caveolin-1 and b-catenin was observed (Figure 4a). Therefore, overexpression of caveolin-1 might stabilize the E-cadherin/b-catenin complex on membranes by suppressing the phosphorylation of b-catenin, which negatively regulate the interaction between E-cadherin and b-catenin (Piedra et al, 2003;Lee et al, 2007;Tominaga et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to IKK-dependent but NF-κB transcription independent control of metastasis, there is also a specifi c link between IKK and angiogenesis. It has been showed that IKKβ upregulates mTOR activity through direct phosphorylation of TSK1 at ser487 and ser511 (Lee et al, 2007).…”
Section: Function Of Stat3 In Inflammation and Cancermentioning
confidence: 99%
“…For instance, TSC and PLD are both modulated by mitogens (e.g., serum and insulin) [40][41][42][43][44][45][46] and TNFα. 15,47 The Ras-Raf-MEK-Erk pathway inhibits TSC2 via phosphorylation by either Erk 48,49 or a downstream kinase Rsk, 50 at the same time PLD activation by Ras [51][52][53][54] or Erk 54,55 has also been suggested. Most recently, our studies have uncovered a direct interaction between Rheb and PLD1.…”
Section: Pld1 As An Effector Of Rheb In Mtorc1 Signalingmentioning
confidence: 99%
“…11 In recent years, the TSC1/TSC2 complex has emerged as a master regulator of mTORC1 signaling in cell growth by serving as a hub for receiving multiple upstream signals, 12,13 including mitogenic stimulation, cellular energy deprivation, hypoxia, inflammatory signals, and oncogenic Wnt signaling [1][2][3][4]14,15 (Fig. 1).…”
Section: Tsc As An Integrator Of Multiple Signals Upstream Of Mtorc1mentioning
confidence: 99%